Representation of women in the magazine "Odbrana"(eng. translate "Defense") of the Ministry of Defense of the Serbian Army - analysis of discourse from a gender perspective - Joksimović Šabaz, Zorana; Cvetkovic, Sreten (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
The empirical basis of the work "Representation of women in the magazine ’Odbrana’ (eng. translate ’Defense’) of the Ministry of Defense of the Serbian Army - analysis of discourse from a gender perspective" stems from the fact that in modern culture there are gender stereotypes and inherited social patterns confirmed and re-placed by the media, those in atypical professions. The aim of this paper is to check the respect of legal measures of gender equality based on the construction of female identity in the representational practice of the chosen medium. Research should offer an understanding of the ways in which media representation renews and produces norms of social life through the prism of the profession. The paper includes research of the content of the magazine "Odbrana" and comparative results that confirm the basic and individual hypotheses. We point out the principle of categorizing women as otherness in the ruling ideologies and their inherent media practices. The methods applied during the research are quantitative and qualitative analysis and critical analysis of discourse. The research corpus includes 2452 newspaper articles. The year 2010 was taken as the first in which the position of women in the army is legally protected, in 2013 in which the implementation of gender content in the magazine should be done in 2020, for an insight into the past decade of inclusive changes. The concluding remarks point to the existence of gender discrimination and propose the fight against gender stereotypes and a turn towards complete freedom of professional choice, achievement and recognition, regardless of gender. The authors of the paper do not deal with the quality of magazine content except exclusively from a gender perspective. The magazine was selected on the basis of the thematic field it deals with and the current laws to which it is subject as a medium independently and as a medium of the institution, a signatory of precisely those laws.